Inter-cycle variability of ignition delay in an ethanol fumigated common rail diesel engine. (1st May 2015) - Bodisco, Timothy; Tröndle, Philipp; Brown, Richard J.
Abstract: An experimental study has been performed to investigate the ignition delay of a modern heavy-duty common-rail diesel engine run with fumigated ethanol substitutions up to 40% on an energy basis. The ignition delay was determined through the use of statistical modelling in a Bayesian framework—this framework allows for the accurate determination of the start of combustion from single consecutive cycles and does not require any differentiation of the in-cylinder pressure signal. At full load the ignition delay has been shown to decrease with increasing ethanol substitutions and evidence of combustion with high ethanol substitutions prior to diesel injection have also been shown experimentally and by modelling. Whereas, at half load increasing ethanol substitutions have increased the ignition delay. A threshold absolute air to fuel ratio (mole basis) of above ∼110 for consistent operation has been determined from the inter-cycle variability of the ignition delay, a result that agrees well with previous research of other in-cylinder parameters and further highlights the correlation between the air to fuel ratio and inter-cycle variability. Numerical modelling to investigate the sensitivity of ethanol combustion has also been performed. It has been shown that ethanol combustion is sensitive to the initial air temperature around the feasible operating conditions of the engine. Moreover, a negative temperature coefficient region of approximately 900–1050 K (the approximate temperature at fuel injection) has been shown with for n -heptane and n -heptane/ethanol blends in the numerical modelling. A consequence of this is that the dominate effect influencing the ignition delay under increasing ethanol substitutions may rather be from an increase in chemical reactions and not from in-cylinder temperature. Further investigation revealed that the chemical reactions at low ethanol substitutions are different compared to the high (>20%) ethanol substitutions. Highlights: Experimental study into the effect of fumigated ethanol on ignition delay. Bayesian modelling to isolate the start of combustion from in-cylinder pressure. Decrease in ignition delay at high engine loads with increasing ethanol substitutions. Perform numerical modelling to explain the experimental results. Identify chemical reactions leading in an ethanol fumigated diesel engine.